Communication skills and leadership behavior of the coach and relationship with technical performance of defensive Soccer players - Abdul Amir, Yusef; Kadhim, Najy (Journal of Physical Education, 2015)
Training process is the important processes that need to be driving towards, achieving the purpose of the Coaches. Leadership is a social process through which is the interaction between the parties to the training process represents the first role of a leader, a coach and the second (player) and is characterized by the coach the ability to influence the players in order to achieve the objectives of the training which is optimized performance for the team. Leadership is a process that involves influence the behavior of the players during the technical performance of the defense to prevent entry of the ball in the Goal. importance of research: lies the consolidation deal coach using the means of communication influential and strengthen the role of leadership behavior that leads to raise the level of technical performance and actual defense players in particular 0. researchers used the descriptive approach was the research sample Premier League clubs were selected 6 clubs way intentional by (81) players, and used instruments and different tools and objective research to identify the communication skills the leadership behavior of the coach. Conclusions: the most important conclusions, the emergence of a significant correlation relationships between communication skills and leadership behavior of coaches and clubs AlKarkh AlKazimiyah and the Aljaish, and moral weakness of others to link these skills and behavior sciences. Recommendations: The most important recommendations, the emphasis on realistic training for the actual technical performance of the defensive and offensive at the same time